Legal Protection in Buying and Selling Goods on the Marketplace - Nailah Sabrina; Rizka Syafriana (ISNU Sumatera Utara, 2025)
The development of digital technology has encouraged people to conduct online buying and selling transactions through marketplaces. However, this system raises various legal issues for both consumers and sellers. This study aims to analyze the forms of legal protection for consumers who receive goods that do not match the description and the urgency of legal protection for sellers who are harmed by the Cash on Delivery (COD) payment system. The method used is a normative-juridical approach with a literature review of relevant laws and regulations and an analysis of cases that occurred on various marketplace platforms. The results show that business actors who send goods that do not match the description can be categorized as committing a breach of contract, while the lack of uniformly regulated COD services causes losses for sellers and couriers. Therefore, legal policy updates are needed to ensure fair and balanced protection for all parties in online buying and selling transactions.